Collective bargaining developments in times of crisis (The Hague, 2017)
"In many EU Member States, the various economic crises of recent years provided grounds for a rarely equalled level of state intervention in the regulation of labour relations with an explicit aim: the decentralisation of collective bargaining. An extensive body of research summed up and analysed expertly in the chapters of this very important book reveals that the process of decentralisation has more often than not led to a situation where salaries and labour conditions are ever more frequently determined by direct negotiations between employer and employees, with the State becoming the sole guarantor of employee protection even as it encourages decreasing labour costs to ensure that companies remain competitive."